Performance of a multi-element (Ag, F, N, W) doped titanium dioxide in the photocatalytic degradation of gaseous formaldehyde under visible light - Laciste, Maricris T. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
In this study, novel multi-element doped TiO2, photocatalysts were synthesized at varying dopant concentration, calcination temperature and calcination time for the degradation of gaseous formaldehyde under visible light irradiation. The performance of the synthesized photocatalysts was examined at varying photocatalyst dosage, initial formaldehyde concentration, light intensity and operating temperature. Photocatalytic degradation of gaseous formaldehyde follows the pseudo first order rate equation based on a Langmuir-Hinshelwood model and was enhanced with greater light intensity and higher operating temperature. Formaldehyde degradation rate improved with pollutant concentration suggesting no mass transfer limitations within the formaldehyde concentration range used. Formaldehyde degradation up to 94% was achieved at 4 ppm formaldehyde concentration and operating temperature of 30°C. The photocatalytic performance of the doped TiO2 was found superior by a 55.8% difference to commercial Degussa P-25 photocatalysts. X-ray diffraction (XRD) analysis of undoped TiO2 showed that mean crystallite size increased with calcination temperature but the trend is reversed for the doped TiO2. Ultraviolet-visible light diffuse reflectance spectrophotometer (UV-Vis DRS) spectra for the doped TiO2 showed absorption cut-off wavelength shifts towards the visible light region. X-ray photoelectron spectroscopy (XPS) results confirmed the incorporation of Ag, F, N, and W in the crystal lattice of TiO2 resulting to binding energy shifts and spin orbit splitting energy variations along increasing calcination temperatures and dopant concentrations. Fourier transform infrared (FTIR) spectra of doped TiO2 showed shifts of OH-bending absorption bands toward increasing wave numbers. Using the sol-gel technique, this work successfully synthesized a novel multielement doped titanium dioxide that is photoactive under visible light illumination with a potential application in indoor air pollution control.
Thesis (Ph.D. in Environmental Engineering)--University of the Philippines, Diliman.
Available only to those bound by confidentiality agreement. Approved written permission required.
Keywords: Air -- Purification -- Photocatalysis -- Philippines; Indoor air pollution -- Philippines